Bioaccumulation of Polycyclic Aromatic Hydrocarbons (PAHs) in Green Mussels (Perna viridis) from Cangio Area, Hochiminh City - Thi Thanh Thuy, Hoang; Luu, Pham Thanh; Loan, Tu Thi Cam; Dong, Nguyen Van; Bao, Le Duy; Yen, Tran Thi Hoang; Huy, Do Xuan (VNU Journal of Science: Earth and Environmental Sciences, 2020)
The bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) in bivalves of the coastal estuary has been investigated since they are favorable seafood. In the present study, the distribution of PAHs was determined in the green mussels ( Perna viridis ) from Cangio area (Hochiminh city). Global comparison showed a lower PAHs accumulated in the green mussels, which ranged between 2.97 to 15.79 ng/g wet weight (ww). However, the presence of carcinogenic isomer (benzo[ a ]pyrene) (up to 0.15 ng/g ww) emphasizes a further monitoring program to ensure the food quality and community health. Keywords:  Polycyclic aromatic hydrocarbons, bioaccumulation, green mussels, Cangio.